2008
DOI: 10.1007/s11144-008-5276-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxides of the IV and VI group metals on the polymorphic transformation of anatase into rutile

Abstract: An effect of some metal oxides on the polymorphic transformation of anatase into rutile and on the rate of dissociation of V 2 O 5 in the systems V 2 O 5 -TiO 2 and V 2 O 5 -TiO 2 -Me x O y has been studied, where Me x O у is SnO 2 , WO 3 , Cr 2 O 3 or ZrO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Above about 475°C, rutile is the major stable phase. However, already Dachille et al (1968), supported by new work (Grzmil et al 2007;Sembaev et al 2008) stress that whole rock composition plays an important role in the variation of the transition to rutile. Smith et al (2009) found that the transition from anatase to rutile is thermodynamically favorable at all temperatures, and the formation of anatase requires lowtemperature aqueous conditions.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…Above about 475°C, rutile is the major stable phase. However, already Dachille et al (1968), supported by new work (Grzmil et al 2007;Sembaev et al 2008) stress that whole rock composition plays an important role in the variation of the transition to rutile. Smith et al (2009) found that the transition from anatase to rutile is thermodynamically favorable at all temperatures, and the formation of anatase requires lowtemperature aqueous conditions.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…On the other hand, the kind of TiO 2 crystal modification influences on the reduction degree of V 2 O 5 upon the heat treatment of V-Ti catalysts. It is known [6], that the thermal dissociation of V 2 O 5 with the formation of VO 2 takes place during the heating of such catalysts. The reduction rate of V 2 O 5 into VO 2 increases with the rise of a treatment temperature.…”
Section: Resultsmentioning
confidence: 99%